SPATIOTEMPORAL ANALYSIS OF NO₂, SO₂, AND CO DISTRIBUTION AFFECTING AIR QUALITY IN GREATER JAKARTA - Robet Triarjunet; Syefiara Hania Yumnaristya; Arif Rohman; Andri N.R Mardiah (Universitas Sebelas Maret (UNS), 2026)
According to the WHO, nearly the entire global population, at approximately 97%, is exposed to air contaminated with pollutants exceeding the WHO guideline threshold. Air pollution results from the coalescence of pollutants with atmospheric air and has become a global challenge, primarily impacting the most significant urban areas worldwide. The Greater Jakarta, or Jabodetabek, is the world's second-largest metropolitan region, with a population of around 34.6 million distributed across 14 municipalities and cities. The high-intensity human activities in Greater Jakarta have severely deteriorated the air quality. This study employs a holistic approach, utilising spatiotemporal analysis and quantitative-descriptive methods to investigate the atmospheric concentrations of CO, NO₂, and SO₂ in Greater Jakarta and its surrounding areas. The spatial distribution patterns of pollutants and their driving factors, including stationary and climatic factors, are investigated during July-December 2023. Results indicated that CO, NO₂, and SO₂ concentrations are significantly above the thresholds defined by the WHO, particularly during the dry season. It is found that the combination of stationary sources, including coal-fired power plants and industrial areas, along with climatic factors, significantly affects pollutant dispersion. These findings underscore the urgent need for stricter emission controls in coal-fired power plants and industrial areas to mitigate the effects of air pollution on public health.